Analisis Kinerja Keuangan Menggunakan Rasio Likuiditas, Rasio Solvabilitas dan Rasio Profitabilitas Pada PT. Pabrik Kertas Tjiwi Kimia Tbk Periode 2021 – 2023 - Abdul Malik; Imam Baidlowi; Yuliasnita Verlandes (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
The purpose of this research is to evaIuate PT. Pabrik Kertas Tjiwi Kimia Tbk's financial performance from 2021 to 2023 utilizing the Iiquidity, soIvency, and profitabiIity ratios. The study's methodology is quantitative descriptive and makes use of descriptive statistics for data analysis. This study's quantitative approach combined with documentation methodologies collects data from PT. Pabrik Kertas Tjiwi Kimia Tbk's yearly financial reports. The annual financial report for the years 2021–2023 is the financial report that was utilized. According to the study's findings, the company's financial performance, as determined by calculating the Iiquidity ratio (current ratio and quick ratio), indicates that it is less liquid and hence less excellent, as seen by its inability to pay off its short-term loans. The firm is deemed to be in excellent financial standing based on the analysis of its solvency ratios, which incIude the debt to equity and debt to asset ratios. Additionally, the company's financing is entirely derived from debt. The profitabiIity ratios, which incIude net profit margin, return on equity, and return on assets, indicate that the firm is not making the most profit possible.